2016
DOI: 10.1016/j.bbmt.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Directed Dosing Leads to Optimized Voriconazole Levels in Pediatric Patients Receiving Hematopoietic Stem Cell Transplantation

Abstract: Invasive fungal infections are a significant cause of morbidity and mortality in recipients of hematopoietic stem cell transplantation (HSCT), warranting antifungal prophylaxis as a standard of care in these patients. Voriconazole is commonly used in this setting because of its broad-spectrum activity and available dosage forms. There is wide well-known inter- and intrapatient variability in voriconazole concentrations, in part because concentrations are affected by common CYP2C19 polymorphisms. In 2 successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…24 A recently published article concluded that a CYP2C19 genotype-directed dosing algorithm (ie, 5, 6 or 7 mg/kg q12 h stratified by CYP2C19 status) allowed pediatric patients (n = 20) to reach target voriconazole concentration significantly sooner than pediatric patients with a standard dosing regimen (5 mg/kg q12 h, n = 25). 26 Of note, the doses evaluated in that publication are lower than those investigated in our studies. It is possible that the use of lower doses in these pediatric patients might be an important factor in the delay of reaching target concentration, in addition to the CYP2C19 polymorphism.…”
Section: Discussionmentioning
confidence: 54%
“…24 A recently published article concluded that a CYP2C19 genotype-directed dosing algorithm (ie, 5, 6 or 7 mg/kg q12 h stratified by CYP2C19 status) allowed pediatric patients (n = 20) to reach target voriconazole concentration significantly sooner than pediatric patients with a standard dosing regimen (5 mg/kg q12 h, n = 25). 26 Of note, the doses evaluated in that publication are lower than those investigated in our studies. It is possible that the use of lower doses in these pediatric patients might be an important factor in the delay of reaching target concentration, in addition to the CYP2C19 polymorphism.…”
Section: Discussionmentioning
confidence: 54%
“…Hence, more studies are needed to address this potential association. While one study did prospectively genotype CYP2C19 and showed a faster achievement of target voriconazole concentrations, this conclusion is limited due to the study’s small size, lack of PMs, and having only a single UM participant in the genotype-directed dosing arm [24]. These issues with the current body of literature warrant further research into this topic given the high morbidity and mortality rates of failed antifungal therapy in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidence for the effect of variants in other genes involved in voriconazole metabolism or concentration, such as CYP3A4 and CYP2C9 , is very limited. One recent study found that dosing voriconazole based on CYP2C19 genotype leads to faster achievement of target concentrations, suggesting that preemptive CYP2C19 genotyping may be useful in the clinic [24]. …”
Section: Pharmacogeneticsmentioning
confidence: 99%
See 2 more Smart Citations